Implementation Of Model View Presenter Design Pattern On Android Based Travel Marketplace Application - Irfan Khoirul Muhlishin,Arna Fariza,Fadilah Fahrul Hardiansyah (International Conference on Industrial Revolution for Polytechnic Education, 2020)
With the increase of complexity of Android application, the structure of application code will be more complex. The complexity is also affected by the lack of features in the Android framework to build applications with a good structure based on programming principles, such as the S.O.L.I.D principle. This complexity often occurs in the main elements of Android app elements, such as Activity and Fragments. Frequently, the two classes have very much functional, such as handling UI / view logic, business logic, to access data. This enormous functionality has made activities and fragments into God Class which is an anti pattern in programming. Therefore it is necessary to have a good architecture with a clear code structure. The one existing architecture and has been applied to other platforms is Model View Presenter / MVP. By applying this design pattern, there is no more classes that have much functionality because UI / view logic functionality handled by view separately, data access handled by model separately, and presenter access model and updating the view based on user interaction. Furthermore by applying Model View Presenter design pattern which is one of implementation of good programming principles such as Separation of Concern and S.O.L.I.D. makes application (marketplace travel) has a good and clear code structure, modular, and maintainable